Security Sector Reform in Lebanon: Consotiationalism, securitization or democratization - Lion Bustillo, Francisco Javier (Cuadernos de Gobierno y Administración Pública, 2019)
Traditionally, the Lebanese Armed Forces (LAF) have been more devoted to the control of Lebanese population than to national defence. At the same time, the control of both the LAF and the many other existing security agencies have been divided among the different political parties according to quotas of confessional affiliation, applying the traditional consotiational Lebanese model. Moreover, there are other non-state actors keeping important weaponry, although some of them (as in the case of Hezbollah) cooperate with the LAF in a very peculiar model of governance. Since the withdrawal of the Syrian troops in 2005, the country is split concerning how to tackle a security sector reform. While some actors only wanted to preserve the status quo (with Syrian and Iranian support), other only want to disarm Hezbollah (backed by the US and Saudi Arabia). The objective of this paper consists of assessing the degree to which the past reforms have contributed to the creation of a security sector adapted to the requirements of a democratic system and able to guarantee domestic peace, political neutrality and national defence.
Keywords: security sector reform, Lebanon, consotiationalism, Lebanese Armed Forces, borders.